Peran Kelompok Etnis dalam Kepemimpinan pada Pemda Provinsi Papua - Soeprapto, Tedjo (Universitas Brawijaya, Indonesia, 2013)
Policies that are not in line with the Special Autonomy under Law No. 21 of 2001 still runs inPapua. Empowerment is still very limited, while the culture of having a dialogue and restructuring policy formats has not been started-up so that the goal to build New Papua New which is more fair, more dignified, and more prosperous cannot be achieved yet. The purpose of this study is to determine the cultural elements of a number of ethnic groups that play a role in the bureaucratic leadership of the Papua ProvincialGovernment. Qualitative method which is symbolic interactionism uses phenomenological perspective to understand this observation. Selected 10 key informants from Papuan leaders consist of 4 (four) senior bureaucrats, 2 (two) researchers and 4 (four) intellectual. From with ten key informants, the researcher explores their opinions and experiences; besides, participant observation, personal experience of theresearcher in the government bureaucracy, and review of literature enriches the depth of this research. The results of this study contribute to the theory of Capacity Building of Government Bureaucracy. The propositions generated are 1.The more we care about the ethnic groups in Papua and understand their culture, then togetherness and unity can be achieved.2. â€The stronger the role of traditional leaders on formal leadership,the implementation of the tasks will be ineffective and inefficient.3.As more leaders do not understand their task and do not understand the culture of the ethnic groups in their environment, it results in the misconduct of their behavior and causes organizational management not well-run. 4.If the leaders obey rules and organizational norms as well as concern on the cultural communities, the organization governance can run effectively and efficiently.